Integrative Motivation of Students in Learning English: Case Study on Rumah Bambu Pintar in Pinrang - Nirwana; Nurhamdah; Mujahidah (Inspiring: English Education Journal, 2020)
This study aims to see the students’ integrative motivation at Rumah Bambu Pintar in Pinrang, the objective of this study is to get the empirical data of the integrative motivation of the students in learning English. The method used in this study is a qualitative method using observation, interview, and documentation.It aimed to know the students’ integrative motivation in learning English. Based on the result, it can be concluded that many students want to speak with native speaker and improve their skill in English, there were one students only want to speak with native speaker, and there were six students want to improve their skill in English such as; writing, listening, speaking, and reading. Many students want to improve their skill in speaking. The students learnt English because they want to know the adaption of word sounds, pronunciations, word orders, and another behavioral in English.